CASES TO BE PROVEN IN THE INVESTIGATION OF THE CRIME OF CULTIVATION OF PROHIBITED CROPS - Komiljonov Hikmatillo Jahongir o’g’li (Web of Journals Publishing, 2024)
The article examines the circumstances that must be clarified during the investigation.Criminal cases related to the illegal circulation of Drugs, Psychotropic Substances and their analogues are important for strengthening the evidence base. It is noted that their timely identification and proof will contribute to a complete, comprehensive and objective examination.
Keywords: provable cases, Drugs, Psychotropic Substances, opening and investigating a crime, sale of drugs without contact, organized criminal group.